Birinci basamak sağlık kuruluşuna başvuran 18 yaş ve üzeri kadınlarda meme ve serviks kanseri taramaları hakkındaki sağlık inançları / Our study aimed to examine the health beliefs about breast cancer and cervical cancer screenings of women aged 18 and over who applied to a primary health care institution using health belief model scales - AKYAY, AYNUR BİLGİN (My University, 2025)
Amaç: Çalışmamızda birinci basamak sağlık kuruluşuna başvuran 18 yaş ve üzeri kadınların meme kanseri ve serviks kanseri taramaları hakkındaki sağlık inançlarını sağlık inanç modeli ölçekleri ile incelemeyi amaçladık. Gereç ve Yöntemler: Çalışmamızı, İstanbul'da bulunan bir aile sağlığı merkezine Mayıs-Temmuz 2024 tarihleri arasında başvuran dahil edilme kriterlerini karşılayan 306 kadının katılımı ile gerçekleştirdik. Katılımcılara; Sosyodemografik Form, Meme Kanseri Taramalarında Sağlık İnanç Modeli Ölçeği ve Rahim Ağzı Kanseri ve Pap Smear Testi Sağlık İnanç Modeli Ölçeği uygulanmıştır. Bulgular: Çalışmaya katılan bireylerin %47.1'i (n=144) üniversite mezunu, %59.8'i (n=183) evli, %30.7'si (n=94) sigara kullanmakta, %61.8'nin (n=189) geliri giderine denk, %14.7'sinin (n=45) ailesinde meme kanseri ve %6.2'sinin (n=19) ailesinde serviks kanseri öyküsü bulunmakta idi. Eğitimin her iki kanser taramaları hakkındaki engel algısını azalttığı, bekar bireylerin yarar algısının daha yüksek olduğu ve taramaları daha çok önemseyip ciddiye aldıkları bulundu. Gelir düzeyinin artması ve ailede kanser öyküsünün bulunmasının, kanser taramalarına yönelik inançları olumlu yönde etkilediği saptandı. Sonuç: Eğitim, medeni durum, gelir ve aile öyküsü faktörlerinin; meme ve serviks kanserleri taramalarına yönelik sağlık inançları üzerinde etkili olduğu görüldü. Kanser taramaları hakkındaki farkındalığı artırmak amacıyla, düşük eğitim seviyesindeki ve düşük gelirli bireylere yönelik eğitim programları düzenlenebilir. Bekar veya ailesinde kanser öyküsü olan bireylere ise sosyal etkinlikler veya destek grupları oluşturulabilir. Anahtar Kelimeler: serviks kanseri, meme kanseri, sağlık inanç modeli, kanser taramaları
SUMMARY Objective: Our study aimed to examine the health beliefs about breast cancer and cervical cancer screenings of women aged 18 and over who applied to a primary health care institution using health belief model scales. Materials and Methods: We conducted our study with the participation of 306 women who met the inclusion criteria and applied to a family health centre in Istanbul between May and July 2024. The participants were administered the Sociodemographic Form, the Health Belief Model Scale for Breast Cancer Screening, and the Cervical Cancer and Pap Smear Test Health Belief Model Scale. Findings: Of the individuals who participated in the study, 47.1% (n=144) were university graduates, 59.8% (n=183) were married, 30.7% (n=94) were smokers, 61.8% (n=189) had income equivalent to expenses, 14.7% (n=45) had a family history of breast cancer and 6.2% (n=19) had a family history of cervical cancer. It was found that education decreased the perception of barriers to screening for both cancers, and single individuals had a higher perception of benefit and took screening more seriously. It was determined that increasing income level and having a family history of cancer positively affected beliefs about cancer screenings. Results: Education, marital status, income and family history factors were found to be effective on health beliefs about breast and cervical cancer screening. In order to increase awareness about cancer screening, educational programmes can be organised for individuals with low education level and low income. Social activities or support groups can be organised for single individuals or individuals with a family history of cancer. Keywords: Breast cancer, cervical cancer, screenings, health belief model scales
Keywords: Aile Hekimliği = Family Medicine